Determinants of waiting times for surgery in older patients with hip fractures: a two-center retrospective study in Japanese acute care hospitals - Yunhan Ji; Takehiro Michikawa; Kenta Zouchi; Kurenai Hachiya; Takumi Taniguchi; Keigo Sato; XiaoJian Ye; Mitsuhiro Morita; Nobuyuki Fujita (BMC Geriatrics)
Abstract Background Hip fractures represent a significant public health issue in an aging society. Early surgical intervention for hip fractures in older adults is associated with fewer complications and higher survival rates, and recent reimbursement incentives in Japan have aimed to encourage surgery within 48 h of injury. However, information on the determinants of delayed surgery, including reimbursement incentives, remains limited. This study aimed to investigate the number of days from admission to surgery and identify factors associated with delayed surgery using data from two acute care hospitals in Japan. Methods We retrospectively analyzed data from 1,209 patients aged ≥ 65 years who underwent hip fracture surgery at two hospitals in Japan between April 2021 and March 2024. Patient- and healthcare system-related factors were compared between patients who underwent surgery within 2 days of admission (E group) and those who underwent surgery at later times (L group). Poisson regression was used to identify independent factors associated with delayed surgery. Results In total, 56% of patients underwent surgery within 2 days of admission. Multivariable analysis identified age ≥ 85 years (prevalence ratio [PR] = 0.81) and trochanteric fracture (PR = 0.81) as factors that reduced the prevalence of delayed surgery. Conversely, diabetes (PR = 1.18); cardiovascular disease (PR = 1.19); low serum albumin levels (PR = 2.08); admission in the pandemic period (PR = 1.26), university hospital (PR = 1.24); and admission on Thursday (PR = 1.69), Friday (PR = 2.99), or Saturday (PR = 2.60) were associated with delayed surgery. The in-hospital mortality rate was approximately 2%, with no significant difference observed between the E and L groups. Conclusions Both patient- and healthcare system–related factors were associated with delayed surgery for hip fractures in older adults. Although a reimbursement incentive has been introduced to promote early surgery, real-world challenges, including preoperative risk factors and hospital resources, continue to affect surgical timing. These findings could help inform strategies to enhance timely surgical care for older patients with hip fractures in aging societies.